김군 - Kang, Sang-woo (South Korea : 1011 Films, 2018)
A photo of a young man taken during the 1980 Gwangju Democratic Uprising in South Korea stirs controversy 35 years after the photo was taken. In 2015, ex-army official Jee Man-won claims that the uprising was not a democratic movement, but a riot perpetrated by North Korean special forces; he believes that the man in the photo was a North Korean special agent, now living in Pyongyang as a national hero. Outraged by Jee's claim, survivors sue him for defamation and distorting the history of the Gwangju Uprising, yet no one remembers the young man in the photo. Finally, someone recognizes him as "Kim-gun", a homeless scrap collector who became one of the leading protesters.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films